Peran Kepemimpinan Dan Budaya Organisasi Dalam Meningkatkan Kinerja Pegawai Sektor Publik Di Kota - Sakinah AS; Anisah Anisah (Universitas Batanghari Jambi, 2020)
This study aims to analyze the influence of leadership and organizational culture on the performance of public sector employees in the city of Jambi. The sample in this study is employees who work in the public sector in the city of Jambi. The data collection method used a questionnaire and analyzed using verification analysis, the analytical tool in this study is using Component Based SEM (Structural Equation Modeling), namely PLS (Partial Least Square). The results of this study will explain whether there is an influence from the main variables studied, namely the leadership, organizational culture and employee performance..